Trends in Vocational Education and Training Research, Vol. III. Proceedings of the European Conference on Educational Research (ECER), Vocational Education and Training Network (VETNET) : Glasgow UK 2020 - Stalder, Barbara E. [Herausgeber]; Nägele, Christof [Herausgeber]; Kersh, Natasha [Herausgeber] (VETNET, 2020)
"The present publication includes more than 30 papers that illustrate planned, ongoing and completed VET research. The papers address initial, continuing and higher vocational education and training, the advancement of individual careers, the education and training of VET educators, and the regional, national and international development of VET through diverse measures. The wide scope of topics positions VET research as a multi-thematic and multi-disciplinary endeavour. VET research addresses questions at the societal, organisational and individual levels - without losing the focus on what's important: to educate and train people and to allow them to fulfil their potential through vocational education and training." (Editor; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; P 3.2.3 Lehrer; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; I 2.3.5 Australien, Ozeanien; Berufsbildung; Berufsbildungsforschung; Berufsbildungssystem; Berufsschullehrer; Lehrerbildung; Berufsausbildung; Betriebliche Integration; Erwachsenenbildung; Höhere Berufsbildung; Sektoraler Qualifikationsrahmen; Flüchtling; Italien; Europa; England; Bundesrepublik Deutschland; Schweiz; Neuseeland; Schweden; Finnland; Litauen; Spanien